Muestra adecuada para la predicción de la asociación diámetro-altura total de Guatteria elata R.E.Fr. "Carahuasca" en bosque natural - Arboretum "El Huayo". Puerto Almendra, Loreto, Perú -2021 - Ruiz Pezo, Tony Alberto (2022)
The study was developed at CIEFOR Puerto Almendra - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the appropriate sample for the prediction of the total diameter-height association of Guatteria elata R.E.Fr. “carahuasca” in natural forest – “El Huayo” Arboretum. Puerto Almendra, Loreto, Peru - 2021. The variables evaluated were the diameter and total height of the trees of the species under study with DAP ? 10 cm; the samples were, Sample 1 (M1) = 30 random data; Sample 2 (M2) with 25 individuals distributed in diameter classes: 10 cm < 15 cm; 15cm < 20cm; 20cm < 25cm; 25 cm < 30 cm and ? 30 cm and Sample 3 (M3) = Representative sample (43 randomly chosen data). The results of the diameter - total height association show that the cubic allometric model was the one with the best fit and the degree of relationship between the variables was good; The equations for the prediction of the diameter-total height relationship are: Sample 1: Y= -9,564 + (2,839 x t) + (-0,096 x t2) + (0,001 x t3); Sample 2: Y= -23,256 + (4,725 x t) + (-0,170 x t2) + (0,002 x t3) and the Representative Sample: Y= -0,754 + (1,728 x t) + (-0,057 x t2) + (0,001 x t3).